Sosialisasi Edukasi Digital Marketing Pada Sekolah SMA/SMK Yapim Taruna Sei Rokan - Bebi Asdilvira; Maulidina; Hidayah Yoanna Putri (Jurnal Masyarakat Indonesia (Jumas), 2024)
This community service was carried out for students of class XII of SMA/SMK Yapim Taruna Sei Rokan. This community service activity was carried out on Wednesday, December 11, 2024. The theme of this community service is the Socialization of Digital Marketing Education at SMA/SMK Yapim Taruna Sei Rokan Schools. Digital marketing is a marketing concept that is carried out using social media to achieve market targets and needs. The community service method is carried out in three ways, namely preparation, implementation, and assessment. The results of this community service activity are expected to provide knowledge and insight as well as soft skills and hard skills to SMA/SMK Yapim Taruna Sei Rokan students, especially in the field of digital marketing so that they can meet the needs of the labor market who are experts and skilled in the field of digital marketing..